2020
DOI: 10.1155/2020/9374896
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Zonation Markers to Identify Liver Functional Disorders

Abstract: A substantial amount of research is being conducted on zonation markers to identify hepatic injuries and disorders based on the structural and functional zonation of the liver. In contrast to metabolic zonation, hepatocyte ploidy reflects the capability of liver regenerative turnover. Nonetheless, many knowledge gaps remain in the understanding of the links between liver disorders and altered zonation and ploidy, partially owing to the lack of sufficient zonation markers. Under this setting, we recapitulated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The finding suggested that tumor hepatocytes of HCC_P subtype presented a higher degree of urea cycle disorder (UCD), which correlated with poor prognosis 47 . Conversely, glycolysis was not a normal functional process of portal and periportal hepatocytes 23,49 , but we observed a slight upregulation of the glycolytic modules in tumor cells of HCC_P patients (Extended Data Fig. 6d).…”
Section: Intermediate State Analysis Reveals a Population Of Tumor Ce...mentioning
confidence: 76%
See 1 more Smart Citation
“…The finding suggested that tumor hepatocytes of HCC_P subtype presented a higher degree of urea cycle disorder (UCD), which correlated with poor prognosis 47 . Conversely, glycolysis was not a normal functional process of portal and periportal hepatocytes 23,49 , but we observed a slight upregulation of the glycolytic modules in tumor cells of HCC_P patients (Extended Data Fig. 6d).…”
Section: Intermediate State Analysis Reveals a Population Of Tumor Ce...mentioning
confidence: 76%
“…The hepatocytes have different states and functions along the CV to PV axis. The lobule can be roughly divided in four regions: central, middle, portal and peri-portal zones 5 (in a few studies the portal and peri-portal zones are combined as a single zone 23,24 ). We annotated hepatocyte zonation utilizing the gene signatures obtained from spatial transcriptomes (Methods, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The liver architecture features a regular arrangement of hexagonal lobules, with each lobule containing periportal zone located at its corners, while the pericentral zone occupies the centre of the lobule. 8 Beyond its structural significance, the liver plays a crucial role as a central organ in governing iron metabolism. 9 Iron is imported into the liver mainly through the transferrin-transferrin receptor system, stored in the form of ferritin and exported by ferroportin (FPN).…”
Section: Introductionmentioning
confidence: 99%
“…The liver architecture features a regular arrangement of hexagonal lobules, with each lobule containing periportal zone located at its corners, while the pericentral zone occupies the centre of the lobule 8 . Beyond its structural significance, the liver plays a crucial role as a central organ in governing iron metabolism 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The liver constitutes one of the largest organs of the body and exerts numerous essential functions associated with digestion, metabolism, protein synthesis and the detoxification of xenobiotics [1]. Hence, the liver is a primary site of various metabolic disorders [2]. Further, chronic hepatitis [3] and metabolic disorders [4] may result in liver fibrosis or even cirrhosis.…”
Section: Introductionmentioning
confidence: 99%